1995
DOI: 10.1093/hsw/20.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Expectations of the Medical Social Worker in the Hospital Setting: Part 2

Abstract: This second part of a survey report focuses on the views of physicians, nurses, and social workers concerning the role of medical social workers in addressing health-related patient problems. All three groups, but particularly physicians and nurses, were more likely to see counseling services as a social worker's job when the client was a family member of the patient, rather than the patient, and when the objective was to modify social-environmental problems of the client rather than to support or modify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…These ages were chosen for several reasons: first, they were plausible in the context of the medical scenarios presented in the vignettes; and second, they spanned the spectrum of childhood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Child's Agementioning
confidence: 99%
“…These ages were chosen for several reasons: first, they were plausible in the context of the medical scenarios presented in the vignettes; and second, they spanned the spectrum of childhood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Child's Agementioning
confidence: 99%
“…In these studies, social workers identified a broader role for themselves, including counseling, than was acknowledged by physicians. More recent studies on perceptions of social work roles in health care (Gross & Gross, 1987;Salvatore, 1988;Cowles & Lefcowitz, 1992Netting & Williams, 1996Egan & Kadushin, 1997) continue to find the resource provision function of social work well understood by physicians and nurses although no longer defined as an exclusive social work responsibility. Work with families was identified as a social work role by a significant number of nonsocial workers, although most did not define counseling of patients as an exclusive role for social work either.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While each discipline may have its own designated primary, secondary, and tertiary competencies, professional competencies overlap, particularly in today's climate of increased trainings and specializations. Research findings indicating strain between physicians, nurses, and social workers (Cowles & Lefcowitz, 1995;Reese & Sontag, 2001) suggests a need for greater role definition and competency measures. During the current investigation, we observed that even teams with high levels of cohesion and familiarity experienced tension regarding task-allocation and role definitions, often between nurses and social workers in regard to psychosocial issues.…”
Section: Conceptual Framework: Interdisciplinary Collaborationmentioning
confidence: 99%